2008
DOI: 10.1590/s0101-81082008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Fatores preditores de resultados no tratamento do transtorno obsessivo-compulsivo com as terapias comportamental e cognitivo-comportamental: uma revisão sistemática

Abstract: INTRODUÇÃO: As terapias comportamental e cognitivo-comportamental reduzem os sintomas do transtorno obsessivo-compulsivo em mais de 70% dos pacientes. Entretanto, cerca de 30% não obtêm nenhuma melhora. Conhecer fatores associados a esses desfechos poderia auxiliar numa melhor indicação do tratamento, incrementando sua eficácia. MÉTODO: Foram revisados trabalhos que investigaram fatores preditivos de resultados nos tratamentos do transtorno obsessivo-compulsivo, nas fontes PubMed, PsycINFO e LILACS. Termos uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As suggested by some authors (6770), the presence of sensory phenomena may predict treatment failure, which can be understood not only by its possible specific neurobiological aspects, but also by the co-occurrence of poor insight (71, 72), which can itself reduce treatment engagement and reduce the chances of an appropriate treatment response. If for psychopharmacological approaches this statement is valid, the presence of sensory phenomena and poor insight leads also to increased rates of nonresponse in psychotherapeutic therapies (39). Moritz et al reported that the presence of sensory phenomena in patients diagnosed with OCD predicts poor insight, but it depends on the type of sensory phenomenon, with special emphasis on visual and tactile phenomena (not analyzed in our study) (71).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As suggested by some authors (6770), the presence of sensory phenomena may predict treatment failure, which can be understood not only by its possible specific neurobiological aspects, but also by the co-occurrence of poor insight (71, 72), which can itself reduce treatment engagement and reduce the chances of an appropriate treatment response. If for psychopharmacological approaches this statement is valid, the presence of sensory phenomena and poor insight leads also to increased rates of nonresponse in psychotherapeutic therapies (39). Moritz et al reported that the presence of sensory phenomena in patients diagnosed with OCD predicts poor insight, but it depends on the type of sensory phenomenon, with special emphasis on visual and tactile phenomena (not analyzed in our study) (71).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroleptics are not the first-choice treatment for OCD, but it seems to be valid as adjuvant when treating resistant or refractory OCD (83), especially atypical neuroleptics, which have augmenting synergism with selective serotonin reuptake inhibitors (SSRIs) because they also have serotonergic action (83, 84). As the CTOC sample is predominantly composed of specialized and tertiary health services, the recruitment of more severe patients, nonresponders to conventional and complex treatments (with comorbidities with tics, for example), may have biased our results, leading to a greater prevalence of the use of these specific medications in these centers (39, 42, 85). As poor insight was related to sensory phenomena, and since sensory phenomena are more prevalent in patients with OCD who also have tics (64, 86), we could speculate a “dopaminergic” modulation of “poor insight.” It could be explained by the facts that tics occur due to dopaminergic dysfunctions involving the basal nuclei, especially striatum and substantia nigra (87, 88), which may result clinically in the increased prescription of drugs with dopaminergic action, such as neuroleptics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raffin et al's. [43] and Keeley et al's. [31], proceeding systematic literature reviews focused on predictive factors of treatment results in OCD, found several studies in which factors associated with a better prognosis with BT or CBT in the treatment of OCD, either associated or not with selective serotonin reuptake inhibitors (SSRI), such as: having a partner [10,49]; greater improvement by the end of treatment [8,21,41]; younger age [21]; being employed [9]; no history of prior treatment [9]; better treatment compliance [13,41]; therapeutic alliance [32]; greater patient motivation for treatment [14,32]; and complete remission of OCS with treatment [8].…”
Section: Introductionmentioning
confidence: 88%